New Approaches to the Management of Organezations in Accordance with the Philosophy of “Vuca - World” - Mezhevov, Alexander; Nikolaev, Viktor; Meleshkin, Mikhail (Տիգրան Մեծ)
The article examines the influence of the “VUCA world” philosophy on the management of a modern organization. The growth of instability and uncertainty in all spheres of life requires specialists of organizations to possess a wide range of knowledge and adequate response to situations when it is impossible to predict the negative development of certain events. The management of organizations needs to abandon mental illusions and established structures in management, maintain their physical and psychological state, work constantly checking with the organisation‟s strategy, and support the team in the correctness of the chosen goals. In the “VUCA world” philosophy, digital technologies have predetermined the emergence of new “flat structures” for solving innovative tasks, assessing and managing counteraction to risks and threats. Contradictions associated with the release of a new product to the market have intensified because, in addition to previously known problems (investment, time and staff resistance), an organization may lose market share of products already produced.
Keywords: Philosophy of economics